Biological role of tumor necrosis factor type α in physiology and pathophysiology - Badowska-Kozakiewicz, Anna (Menopause Review/Przegląd Menopauzalny, 2013)
Tumor necrosis factor α (TNF-α) is a pleiotropic and proinflammatory cytokine with anticancer cytotoxic activity. Tumor necrosis factor is a multifunctional cytokine involved in various cell functions, such as differentiation, mitosis, angiogenesis, inflammation and immune controls. TNF-α plays also an important role in the control of metabolism. TNF-α is a recognized mediator of insulin resistance, which is the best examined link in the pathogenesis of polycystic ovary syndrome (PCOS). Studies in which an assessment of the polymorphism in the TNF-α and its receptor – TNFR2 was performed, no significant correlation between the 308 region of the gene polymorphism of TNF-α and the occurrence of PCOS was found. Women with obesity, but also lean women with polycystic ovary syndrome, had increased levels of TNF-α in serum, which correlated with positive weight, and negatively with insulin sensitivity. On this basis, one can assume that TNF-α is an important element connecting obesity with insulin resistance, and this may be important in the pathogenesis of PCOS. Myometrium conversion into leiomyoma and an increase in its mass are accompanied by changes in the expression and content of TNF-α. Proinflammatory cytokine – TNF-α has been shown to be an important factor during development and maintenance of intestinal inflammation in inflammatory bowel disease. Due to the activity of TNF-α it can be said that it is a multifunctional cytokine, and we see its involvement in cellular functions such as differentiation, mitosis, angiogenesis, inflammation and immune regulation.